THE NEED FOR THE ORIGIN, EMERGENCE AND FORMATION OF PEDAGOGICAL TECHNOLOGIES - Khatamova , Zumrad Nazirjonovna; Islamov, Komiljon Yunusali o‘g‘li (Educational Research in Universal Sciences, 2023)
In the article, the concept of pedagogical technology, its factors of origin, necessity are discussed, and the necessity of its formation is also touched upon.